2012
DOI: 10.1111/j.1348-0421.2012.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal superantigen‐like protein 10 binds to phosphatidylserine and apoptotic cells

Abstract: Staphylococcal superantigen‐like proteins (SSLs) are a family of exoproteins that have structural similarities to staphylococcal superantigens. Although SSLs do not have superantigenic activity, some of them have been reported to bind to host immune related molecules and they have been implicated in immune evasion by S. aureus. In this study, we showed that SSL10 is capable of binding to phospholipids. SSL10 bound to phosphatidylserine (PS) containing liposome, but not to phosphatidylcholine liposome. SSL10, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…5). We previously reported that SSL10 is able to bind phosphatidylserine (17). It is possible that SSL10 bridges prothrombin with phospholipid in the absence of Ca 2ϩ , but the present data exclude this possibility.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…5). We previously reported that SSL10 is able to bind phosphatidylserine (17). It is possible that SSL10 bridges prothrombin with phospholipid in the absence of Ca 2ϩ , but the present data exclude this possibility.…”
Section: Discussioncontrasting
confidence: 64%
“…The competitive effect of Ca 2ϩ on SSL10-prothrombin interaction was limited at 1.25 mM of Ca 2ϩ ; therefore, the interaction between SSL10 and prothrombin will be significant in physiological conditions. We previously reported that SSL10 binds to PS (17). Recombinant GST-annexin V, which interacts with PS, did not bind to SSL10 (data not shown), suggesting that the PS-binding feature does not account for the binding of SSL10 to prothrombin.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…SSL10 binds 1:1 with immunoglobulin of the IgG1 subclass with an affinity of 300 nM and a specificity that is restricted to human and primates [376,377]. Binding of SSL10 to fibrinogen, fibronectin [377], CXCR4 [378], phosphatidylserine [379], prothrombin, and factor Xa [380] has also been observed. SSL10 secreted by S. aureus into its immediate environment binds to IgG1, the most abundant of the four human IgG subclasses found in the blood which also has the highest affinity for multiple FcγRs [390].…”
Section: The Immunoglobulin/complement-inhibiting Sslsmentioning
confidence: 85%